DESULFURIZATION OF STEEL IN CONDITIONS OF GUP «LPZ». DEVELOPMENT OF RECOMMENDA¬TIONS ON INCREASE OF ITS EFFICIENCY - V. A. Chajkin; A. V. Chajkin; K. A. Myagkov; V. V. Ishutin (Литьë и металлургия)
The analysis of sulphur removal of steels in the stove-busket is carried out. Besides, statistical processing of quantities of flux metals and ferroalloys, given to the stove-busket at various stages of melting which has confirmed the assumption of economy of ferroalloys due to additional processing deoxidizing mixtures, is carried out.